2014
DOI: 10.4172/2157-7633.1000162
|View full text |Cite
|
Sign up to set email alerts
|

Adult Stem Cell Therapy in Chronic Wound Healing

Abstract: Normal wound healing is a dynamic and complex process involving coordinated interactions between diverse immunological and biological systems. If a wound does not heal in an orderly and timely sequence, or if the healing process does not result in structural integrity, then the wound is considered chronic. It is easy to define a chronic wound, but finding a solution is a complicated matter. Conventional treatment of chronic wounds does not seem to work in several cases, so it is necessary to develop different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 75 publications
0
20
0
Order By: Relevance
“…These results have implications for the treatment of chronic wounds as BM-MPCs not only promote neovascularization but also produce antiinflammatory cytokines that have the potential to advance chronic wounds past the chronic low-grade inflammation typically associated with poorly healing diabetic ulcers. [35][36][37] Several methods have previously been used to recruit endogenous progenitor cells, including injection of cytokines involved in stem cell homing, such as SDF or HGF, and gene therapy. 32,38 Polymeric hydrogels seeded with stem cells, however, display several advantages over these methods.…”
Section: Discussionmentioning
confidence: 99%
“…These results have implications for the treatment of chronic wounds as BM-MPCs not only promote neovascularization but also produce antiinflammatory cytokines that have the potential to advance chronic wounds past the chronic low-grade inflammation typically associated with poorly healing diabetic ulcers. [35][36][37] Several methods have previously been used to recruit endogenous progenitor cells, including injection of cytokines involved in stem cell homing, such as SDF or HGF, and gene therapy. 32,38 Polymeric hydrogels seeded with stem cells, however, display several advantages over these methods.…”
Section: Discussionmentioning
confidence: 99%
“…Different cell types and methods can be employed in the stem cell therapy for wound healing and Branski et al have provided a detailed outline of these technologies. Bone marrow‐derived stem cells (BMSCs) are probably the most studied marrow‐derived stem cells (MSCs), and several clinical studies have demonstrated their usefulness in wound healing . However, bone marrow harvesting is an invasive and painful procedure and some pathologic conditions (e.g., severe burn trauma, sepsis, silver sulfadiazine toxicity, or old age) can reduce the BMSCs availability …”
Section: Advanced Dressings Containing Biological Agentsmentioning
confidence: 99%
“…Bone marrow-derived stem cells (BMSCs) are probably the most studied marrow-derived stem cells (MSCs), and several clinical studies have demonstrated their usefulness in wound healing. 228,229 However, bone marrow harvesting is an invasive and painful procedure and some pathologic conditions (e.g., severe burn trauma, sepsis, silver sulfadiazine toxicity, or old age) can reduce the BMSCs availability. 227 Adipose-derived stem cells (ADSCs) are considered an interesting alternative to BMSCs for wound healing application because they express a similar array of cytokines and GFs and can be easily isolated from sections of whole fat (biopsy) or lipoaspirate, which means a less aggressive and painful harvesting procedure.…”
Section: Stem Cellsmentioning
confidence: 99%
“…[1,2] Once the damage of skin tissue occurs, the repair process appears to be very complex, [3][4][5] which includes four interactive and classic phases: hemostasis, inflammation, proliferation, and remodeling/maturation. [6] Although most skin defect can be quickly and effectively healed within 1 or 2 weeks, [7,8] the extensive full-thickness wounds are often hard to repair, which presents serious impact on health and even threaten people's life. [9] Therefore, a variety of biomaterials have been developed as wound dressings, such as nanofibers, sponge, foam, and hydrogels.…”
Section: Introductionmentioning
confidence: 99%